ANALISIS FAKTOR-FAKTOR BAURAN PEMASARAN YANG MENENTUKAN KEPUTUSAN KONSUMEN DALAM MEMILIH MINIMARKET UNTUK BERBELANJA DI DESA UNGASAN - Jagatkirana, I Made Ari Kharismananda; Sandyasmara, Cokorda Anom Bayu; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): September, 2022)
The increasing number of minimarkets in Ungasan Village causing the income of grocery store owners decreases, that makes grocery stall owners should implement a marketing mix strategy to be compete, by studying the behavior of minimarket consumers. This study aims to analyze the marketing mix factors that determine consumer decisions in choosing a minimarket to shop in Ungasan Village and find out the dominant factors so the results is expected to help grocery store owners in Ungasan Village. The stages of this study including preliminary survey, attribute identification based on marketing mix factors, questionnaire generating, reliability and validity testing, broadcasting the questionnaire to the consumers of grocery store, data gathering, data analyzing, and generating the results and the discussions. The study implemented by surveying 154 respondents, then from the results a factor analysis carried out using Microsoft Excel 2016 and SPSS 26. The results show that there are five factors betwixt accessibility factor, employee performance factor, promotion factor, physical evidence factor, and price factor. The accessibility factor is the dominant factor that determines consumer decisions in choosing a minimarket for shopping, with the attribute that has the highest correlation value is that the distance of the mini market is close to the dwelling (X8).